Analisis Kesantunan Berbahasa dalam Pertanyaan Interogasi BAP: Kajian Linguistik Forensik dan DampakPsikologis pada Saksi - Saud, Jefriyanto; Lustyantie, Ninuk; Murtadho, Fathiaty (LPPM Institut Pendidikan Nusantara Global, 2025)
The language in the Police Investigation Report (BAP) is very important, yet interrogations in Indonesia often neglect politeness, resulting in suggestive and intimidating questions that can pressure witnesses, damage their